Aborsi Sebuah Perdebatan Filsafat Hukum (Lex Jurnalica, 2014)
AbstractAbortion is a simple word that raises a philosophical debate. The act of abortion in the dynamics of natural law moralists debate dealing with the feminist as a supporter of feminist legal theory. Each party to this day continue to look for new spaces in an effort in an effort to find new meaning the act of abortion. The feminist who supports full rights for the reproduction of gender relations as similarities in dealing with the moralists as moral support. In the other hand the values of Islamic theology also raises ethical ideas and the act of abortion.Keywords: abortion, philosophical debate, moral and the rights of reproductionÂ Â AbstrakAborsi merupakan kalimat yang sederhana yang telah menimbulkan perdebatan filosofis.Perbuatan aborsi dalam dinamika hukum alam, menimbulkan perdebatan antara pendukung moral hukum alam dengan pendukung feminist legal theory.Masing-masing pihak berusaha memberikan pemaknaan-pemaknaan atas arti aborsi. Kaum feminist yang mendukung hak reproduksi dalam kaitan relasi gender berhadapan dengan moral dalam prinsip Hukum Alam. Pada sisi yang lain terdapat nilai-nilai Teologi Islam yang juga memiliki nilai etis atas perilaku aborsiKata kunci: aborsi, perdebatan filsafat, moral dan hak reproduksi